Mixed metal oxide: a new class of catalyst for methanol activation - Mehta, Shweta; Agarwal, Sheena; Kenge, Nivedita; Mekala, Siva Prasad; Patil, Vipul; Raja, T.; Joshi, Kavita (Applied Surface Science, 2020)
In this work, we propose a mixed metal oxide as a catalyst and demonstrate it's ability to not only activate the MeOH molecule upon adsorption but also dissociate O-H and one of it's C-H bonds. MeOH activation is compared on two prominent facets of ZnAl(2)O(4 )viz. (2 2 0) and (31 1). While spontaneous O-H bond dissociation is observed on both facets, C-H bond dissociates only on the (3 1 1) surface. Multiple factors like atomic arrangement and steps on the surface, coordination of surface atoms, and their effective charges have a combined effect on MeOH activation. The (3 1 1) surface offers higher catalytic activity in comparison with (2 2 0) surface. Having a stepped surface, availability of multiple sites, and variation in the charge distribution are some of the reasons for better catalytic performance of (3 1 1) facet. Effect of orientation of MeOH with respect to the surface adds both, information and complexity to the problem. Observations pertinent to understanding this effect are also reported. A detailed analysis of atomic arrangement on the two surfaces provides a rationale as to why MeOH gets dissociated spontaneously on the mixed metal oxide. The promising results reported here opens up a new class of catalyst for research.
Keywords: DFT; MeOH; Spontaneous dissociation; ZnAl2O4

Understanding the ML black box with simple descriptors to predict cluster-adsorbate interaction energy - Agarwal, Sheena; Mehta, Shweta; Joshi, Kavita (New Journal of Chemistry, 2020)
Density functional theory (DFT) is currently one of the most accurate and yet practical theories used to gain insight into the properties of materials. Although successful, the computational cost required is still the main hurdle even today. In recent years, there has been a trend of combining DFT with Machine Learning (ML) to reduce the computational cost without compromising accuracy. Finding the right set of descriptors that are simple to understand in terms of giving insights about the problem at hand, lies at the heart of any ML problem. In this work, we demonstrate the use of nearest neighbor (NN) distances as descriptors to predict the interaction energy between the cluster and an adsorbate. The model is trained over a size range of 5 to 75 atom clusters. When the training and testing is carried out on mutually exclusive cluster sizes, the mean absolute error (MAE) in predicting the interaction energy is similar to 0.24 eV. MAE reduces to 0.1 eV when testing and training sets include information from the complete range. Furthermore, when the same set of descriptors are tested over individual sizes, the MAE further reduces to similar to 0.05 eV. We bring out the correlation between dispersion in the nearest neighbor distances and variation in MAE for individual sizes. Our detailed and extensive DFT calculations provide a rationale as to why nearest neighbor distances work so well. Finally, we also demonstrate the transferability of the ML model by applying the same recipe of descriptors to systems of different elements like (Na-10), bimetallic systems (Al6Ga6, Li4Sn6, and Au40Cu40) and also different adsorbates (N-2, O-2, and CO).

Copolymers of bipyridinium and metal (Zn & Ni) porphyrin derivatives; theoretical insights and electrochemical activity towards CO2 - Kochrekar, Sachin; Kalekar, Ajit; Mehta, Shweta; Damlin, Pia; Salomaki, Mikko; Granroth, Sari; Meltola, Niko; Joshi, Kavita; Kvarnstrom, Carita (RSC Advances, 2021)
This study reports the electropolymerization of novel keto functionalized octaethyl metal porphyrins (Zn2+ and Ni2+) in the presence of 4,4 `-bipyridine (4,4 `-bpy) as a bridging nucleophile. The polymer films were characterized by electrochemical, spectroscopic (UV-Vis, XPS, FT-IR and Raman spectroscopy) and imaging (AFM and SEM) techniques. The absorption and electronic spectra confirm the presence of both porphyrin and 4,4 `-bipyridine units in the film. The surface morphology reveals homogeneous film deposition with average roughness values of approx. 8 nm. The theoretical studies performed offered insights into the interplay of different metal centres (Zn2+ and Ni2+) and the keto functionality of the porphyrin unit in the formation of copolymer films. The electrochemical interaction of polymer films with CO2 suggests a reversible trap and release of CO2 with low energy barriers for both the polymers.

From molecular adsorption to decomposition of methanol on various ZnO facets: a periodic DFT study - Mehta, Shweta; Joshi, Kavita (Applied Surface Science, 2022)
Methanol is an interesting and important molecule to study because of its potential to replace existing fuels. It is also a prominent hydrogen source which can be used to generate hydrogen in-situ. ZnO is widely used as catalyst in synthesis of methanol from CO2 at industrial scale. In this work, we demonstrate that the same catalyst could be used for MeOH decomposition. We have investigated interaction of methanol with various flat and stepped facets of ZnO by employing Density Functional Theory (DFT). Two flat [(10(1)overbar 0) and (11(2)overbar 0)] and two stepped [(10(1)overbar 3) and (11(2)overbar 2)] facets are studied in detail for methanol adsorption. Chemisorption of MeOH with varying strength is common to all four facets. Most importantly spontaneous dissociation of O-H bond of methanol is observed on all facets except (11(2)overbar 0). Our DFT calculations reveal that molecular adsorption is favored on flat facets, while dissociation is favored on step facets. Also, (10(1)overbar 0) facet undergoes substantial reconstruction upon MeOH adsorption. Activation of C-H bond along with strengthening of C-O bond on ZnO facets suggest partial oxidation of methanol. With our DFT investigations, we dig deeper into the underlying electronic structure of various facets of ZnO and provide rationale for the observed facet dependent interaction of ZnO with MeOH.
Keywords: DFT; MeOH; Surface interactions; ZnO

Pseudo-boehmite AlOOH supported NGr composite-based air electrode for mechanically rechargeable Zn-air battery applications - Kharabe, Geeta Pandurang; Manna, Narugopal; Nadeema, Ayasha; Singh, Santosh K.; Mehta, Shweta; Nair, Aathira; Joshi, Kavita; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2022)
Both mechanically and electrically rechargeable zinc-air batteries (ZABs) have received much interest due to their high energy density and suitability for mobile and stationary applications. However, their commercialization has been impeded by the lack of robust, low-cost and environmentally benign catalyst materials that can be easily scaled up. In this context, the present work introduces a new type of transition metal-free catalytic material (AlOOH/NGr) by anchoring the pseudo-boehmite phase of aluminium oxyhydroxide (AlOOH) nanosheets over nitrogen-doped graphene (NGr) via a single-step and straightforward hydrothermal process. Furthermore, density functional theory (DFT) based computation demonstrates that the nucleation of AlOOH starts from the N-sites and points towards the strong surface interaction between AlOOH and NGr via doped nitrogen. AlOOH/NGr consisting of thin layered pseudo-boehmite sheets uniformly distributed over NGr has displayed an oxygen reduction reaction onset potential of 0.83 V and a half-wave potential of 0.72 V, along with good catalytic durability in alkaline medium. With this, AlOOH/NGr, when used as an air electrode for fabricating a primary Zn-air battery, the system has exhibited an open circuit voltage of similar to 1.27 V with a flat discharge profile at a current rate of 10 mA cm(-2). The fabricated system delivered a specific capacity of similar to 720 mA h g(-1) and a high power density of 204 mW cm(-2) and is comparable to the counterpart system based on the state-of-the-art Pt/C (20 wt% Pt) cathode. Additionally, the homemade battery was able to maintain its performance after 4 times of mechanical recharging of the battery, which lasted for more than 35 h at a discharge current density of 10 mA cm(-2). Thus, we have uncovered the potential of an earth-abundant metal-based catalytic system for fabricating and demonstrating a robust mechanically rechargeable zinc-air battery.

Electronic fingerprints for diverse interactions of methanol with various Zn-based systems - Mehta, Shweta; Joshi, Kavita (Surface Science, 2023)
We have investigated various Zn-based catalysts for their interaction with methanol (MeOH). MeOH is one of the most critical molecules being studied extensively, and Zn-based catalysts are widely used in many industrially relevant reactions involving MeOH. We note that the same element (Zn and O, in the present study) exhibits different catalytic activity in different environments. The changing environment is captured in the underlying electronic structure of the catalysts. In the present work, we compared the electronic structure of Zn-based systems, i.e., ZnAl2O4 and ZnO along with oxygen preadsorbed Zn (O-Zn) and metallic Zn. We demonstrate the one-to-one correlation between the pDOS of the bare facet and the outcome of that facet's interaction (i.e. either adsorption or dissociation of MeOH) with MeOH. These findings would pave the way towards the in-silico design of catalysts.
Keywords: DFT; Electronic properties; Methanol; Zn-based systems; ZnO

Hydrogen from catalytic non-thermal plasma-assisted steam methane reforming reaction - Bajpai, Abhinav; Mehta, Shweta; Joshi, Kavita; Kumar, Sushant (International Journal of Hydrogen Energy, 2023)
Steam methane reforming reaction was carried out in a dielectric barrier plasma reactor. A systematic study is conducted to understand the influence of input power, flow rate, and water for the conversion, yield, and selectivity of the reaction over strategically designed catalysts. In particular, the production rate and selectivity of the products (H2, CO and C2 hydrocarbons) are monitored. CeO2 was used as packing material, mixed with oxides of manganese or copper and their combination. The optimum Cu/CeO2 catalyst illustrated the production rate of 248.7 mmolg-1h-1 and 11.25 mmolg-1h-1 for H2, and CO, respectively at specific energy input of 19.8 JL-1. DFT calculations exhibit apparent change in electronic structure of the CeO2 after inclusion of oxides of manganese and copper that enhance interaction with methane. Based on these findings, a plausible mechanism is elucidatedSteam methane reforming reaction was carried out in a dielectric barrier plasma reactor. A systematic study is conducted to understand the influence of input power, flow rate, and water for the conversion, yield, and selectivity of the reaction over strategically designed catalysts. In particular, the production rate and selectivity of the products (H2, CO and C2 hydrocarbons) are monitored. CeO2 was used as packing material, mixed with oxides of manganese or copper and their combination. The optimum Cu/CeO2 catalyst illustrated the production rate of 248.7 mmolg-1h-1 and 11.25 mmolg-1h-1 for H2, and CO, respectively at specific energy input of 19.8 JL-1. DFT calculations exhibit apparent change in electronic structure of the CeO2 after inclusion of oxides of manganese and copper that enhance interaction with methane. Based on these findings, a plausible mechanism is elucidated which can help to design catalyst for other applications in non-thermal plasma atmosphere. & COPY; 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: DFT; Dielectric barrier discharge; Non-thermal plasma; selectivity; Specific energy input; Steam methane reforming

From digital blueprint to chemical reality: methanol to formaldehyde at ambient conditions - Mehta, Shweta; Kasabe, Mirabai; Umbarkar, Shubhangi B.; Joshi, Kavita (Applied Surface Science, 2024)
Partial oxidation of methanol to value added product presents an intriguing yet challenging process. Among these products, formaldehyde is the simplest and one of the most vital aliphatic aldehydes, which has extensive application across various domains. Industrially, silver and iron-molybdenum oxides are used as catalysts for the conversion of methanol to formaldehyde at elevated temperatures (600 degrees C and 250-400 degrees C, respectively). However, in this computational and experimental study, we have demonstrated the efficacy of ZnO as a catalyst. Notably, in the presence of ZnO, methanol readily converts to formaldehyde even under ambient conditions. We employed periodic density functional theory (DFT) to explore (10 1 1) facet of ZnO to elucidate its interaction with methanol. Our comprehensive analysis identified the most active facet (10 1 1) involved in the spontaneous conversion of methanol to formaldehyde. Subsequently, experimental validation supported our theoretical findings, demonstrating the conversion of methanol to formaldehyde with 100% selectivity at room temperature and atmospheric pressure in the presence of ZnO. This study exemplifies the pivotal role of theory in catalyst design.
Keywords: DFT; Formaldehyde; MeOH; ZnO

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: sustainable high current density electrolysis - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Vijay, Pothoppurathu M.; Nalajala, Naresh; Mehta, Shweta; Joshi, Kavita; Ravindranathan, Sapna; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Current study elucidates the electrocatalytic efficacy of palladium-nanocubes (Pd-NCs) for the selective oxidation of glucose to value-added chemicals with concomitant hydrogen evolution. The Pd-NC catalyst demonstrated exceptional activity and product selectivity, achieving nearly quantitative glucose conversion (>99 %) with high gluconic and glucaric acid yield at low anodic overpotential (0.6 V vs. RHE) in alkaline electrolyte. At not-so-high elevated potentials (1.2 V vs. RHE), oxidative CC scission prevails, yielding shorter-chain carboxylates along with C6-acids. Reaction products are thoroughly characterized and quantitatively estimated by NMR spectral methods; NMR methods also provide CC cleavage and mechanistic pathways of glucose to various products. Complementary DFT calculations delineate the thermodynamic favorability of glucose adsorption on Pd-NC surfaces (-1.83 eV) and the exergonic oxidation pathway under applied bias, corroborating experimental product distributions. In a two-electrode electrolyzer, Pd-NC anode paired with Pt/C and Ni2P cathode demonstrates 100 mA/cm(2) at 0.99 V and 1.37 V, respectively, with 48 % reduction in energy input (26.6 kWh/kg H-2) compared to conventional alkaline electrolysis; critically, H-2 production energy is lower than the usable energy (33.3 kWh/kg H-2). Sustainable chronopotentiometric assays confirm sustainability (similar to 140 h) in alkaline as well as saline electrolytes, underscoring the system's resilience against chloride-mediated corrosion. Present work establishes a proof of concept for integrated biomass-component valorization and carbon-negative green hydrogen production, merging atomic-level mechanistic insights with scalable reactor design. Optimization of reaction parameters, including potential tuning, reaction temperature and electrolyte engineering, offers a compelling strategy to further enhance C6 and fragmented product selectivity and overall system efficiency.
Keywords: biomass valorization; electrocatalysis; energy conversion; Sustainability